2013
DOI: 10.1111/epi.12474
|View full text |Cite
|
Sign up to set email alerts
|

In vivo treatment with the casein kinase 2 inhibitor 4,5,6,7‐tetrabromotriazole augments the slow afterhyperpolarizing potential and prevents acute epileptiform activity

Abstract: SUMMARYObjective: The slow afterhyperpolarizing potential (sAHP) following prolonged depolarization is a major intrinsic mechanism of neuronal inhibition, by powerfully dampening excitability for up to 2 s. Therefore, an altered sAHP function might be vulnerable to hyperexcitable states such as epilepsy. Here, we have investigated the role of casein kinase 2 (CK2) on the sAHP in control and chronically epileptic tissue. Methods: Using the rat pilocarpine model of chronic temporal lobe epilepsy, we performed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Because CA1 pyramidal cells are the main output channel from the hippocampus to the cortex (Witter, Wouterlood, Naber, & Van Haeften, ), their intrinsic excitability likely determines multiple brain functions. Indeed, changes in sAHP amplitude in these neurons have been implicated in learning and memory (Disterhoft, Wu, & Ohno, ; Brosh, Rosenblum, & Barkai, ; Zelcer et al, ; Zhang, Ouyang, Ganellin, & Thomas, ; Thomas, ), in cognitive decline in aging (Moyer, Power, Thompson, & Disterhoft, ; Disterhoft et al, ; Matthews, Linardakis, & Disterhoft, ) and in epileptogenesis (Brehme, Kirschstein, Schulz, & Köhling, ; Tamir, Daninos, & Yaari, ). Assuming an important role of ΝΚΑs in sAHP generation in vivo, it is very likely that these changes involve modulation of NKA activity through multiple signaling pathways (Ewart & Klip, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because CA1 pyramidal cells are the main output channel from the hippocampus to the cortex (Witter, Wouterlood, Naber, & Van Haeften, ), their intrinsic excitability likely determines multiple brain functions. Indeed, changes in sAHP amplitude in these neurons have been implicated in learning and memory (Disterhoft, Wu, & Ohno, ; Brosh, Rosenblum, & Barkai, ; Zelcer et al, ; Zhang, Ouyang, Ganellin, & Thomas, ; Thomas, ), in cognitive decline in aging (Moyer, Power, Thompson, & Disterhoft, ; Disterhoft et al, ; Matthews, Linardakis, & Disterhoft, ) and in epileptogenesis (Brehme, Kirschstein, Schulz, & Köhling, ; Tamir, Daninos, & Yaari, ). Assuming an important role of ΝΚΑs in sAHP generation in vivo, it is very likely that these changes involve modulation of NKA activity through multiple signaling pathways (Ewart & Klip, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, since pharmacological HCN channel inhibition by ZD7288 that does not distinguish between HCN isoforms led to an increase of sAHP-mediating currents (Gu et al, 2005), we propose that a net enhancement of HCN channel function by TBB could have antagonized an expected TBB-mediated sAHP increase due to enhanced K Ca 2 function. In fact, we previously found that the sAHP was increased in control and epileptic tissue when animals were pretreated in vivo with TBB (Brehme et al, 2014). On the one hand, this could be simply due to different recording procedures (isolated cells versus slice experiments) that differ with respect to recording from dendritic compartments expressing high levels of HCN1 (Nolan et al, 2004).…”
Section: Increased K Ca 2 Function As the Relevant Disease Modifying mentioning
confidence: 98%
“…Only cells with an RMP of −50 mV or more negative were included in this study. The AHP-mediating K + current and charge transfer were measured in the voltage-clamp mode as previously described (Brehme et al, 2014). In brief, the recording solution contained 500 nM tetrodotoxin (TTX) and 1 mM tetraethylammonium (TEA) (both from Tocris Bioscience, Bristol, United Kingdom) to block voltage-activated Na + and K + channels, respectively.…”
Section: Patch-clamp Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting SK channels leads to massive exacerbation of epileptiform activity in hippocampal slices of chronically epileptic rats but not in control tissue (Schulz et al 2012). Not only is the mAHP reduced in this tissue, but also the sAHP (Brehme et al 2014). The mAHP reduction can be restored by blocking casein-kinase 2 (CK2), a major kinase for calmodulin phosphorylation.…”
Section: Calcium-and Sodium-activated Potassium Channelsmentioning
confidence: 99%